Gas hydrate accumulation in shelf break setting: Example from the Qiongdongnan Basin in the northern slope of the South China Sea. Issue 3 (30th November 2021) - Zhang, Wei; Liang, Jinqiang; Zhang, Ruwei; Deng, Wei; Gu, Yuan; He, Yulin; Gong, Yuehua; Meng, Miaomiao; Feng, Junxi; Liang, Jin
Abstract : Based on interpretation and inversion of high‐resolution seismic data, a previously undocumented occurrence of pore‐filled gas hydrates that are associated with a submarine canyon system was discovered in the shelf break of the north‐east Qiongdongnan Basin (QDNB) in the northern South China Sea (SCS). Continuous bottom simulating reflections (BSRs) were recognized in the submarine striking NW‐SE ridges along the shelf break. The two‐way travel times (TWTs) of the BSRs are about 200–250 ms below the sea floor and the burial depths are mapped at ~180–225 mbsf after time‐depth conversion. The distribution of the enhanced reflections (ERs) and acoustic blanking zone overlying the BSRs indicate possible pore‐filled gas hydrate enrichment. ERs have been commonly observed immediately below the BSRs, indicating the accumulation of free gas, which exhibits distinct amplitude versus offset (AVO) anomalies. The acoustic impedance inversion results show that the gas hydrate saturation is 20–50%, and the thickness of the gas hydrate‐bearing layers is usually ~10–40 m, with a maximum thickness of up to ~90 m in local regions. Large‐scale listric faults originating from the deep sag connect the hydrocarbon source region and the shallow gas hydrate stability zone (GHSZ) and act as migration pathways for biogenic gas and potentially thermogenic gas. In addition, hydrocarbons may also be transported into the GHSZ along the sidewalls of the canyon. Canyon incision is believed to cause the increase in the burial depth of the BSRs on the flank of the ridge toward the base of the channel and thereby to trap the hydrocarbons migrating along the sidewall in permeable beds due to the decrease in permeability caused by the gas hydrate accumulation, resulting in the occurrence of ERs immediately below the BSRs. It is speculated that in the channel‐levee system, the coarse‐grained sediments should be deposited within the GHSZ, and the reservoir's physical properties are conducive to the wide distribution and enrichment of pore‐filled gas hydrates in the shelf break of the northern QDNB. Abstract : A new occurrence of pore‐filled gas hydrates that are associated with a submarine canyon system was discovered in the shelf break of the Qiongdongnan Basin (QDNB) in the South China Sea (SCS). Continuous bottom simulating reflections (BSRs) accompanying with free gas were recognized in the submarine ridges along the shelf break. The acoustic impedance inversion results show that the hydrate saturation is 20–50%, and the thickness of the hydrate‐bearing layers is usually ~10–40 m. Large‐scale listric faults originating from the deep sag connect the hydrocarbon source region and the gas hydrate stability zone (GHSZ) and act as migration pathways for biogenic gas and potentially thermogenic gas. Canyon incision is believed to cause the downward migration of the BSRs on the flank of the ridge toward the base of the channel and thereby to trap the hydrocarbons due to the decrease in permeability caused by the hydrate accumulation. The filling and erosion of the channel may induce the adjustment of the physical equilibrium of the hydrate at present. It is speculated that in the channel‐levee system, the coarse‐grained sediments with favourable physical properties are conducive to the wide distribution and enrichment of pore‐filled gas hydrates with great exploration prospects.